Laser Activation of Isotope Selective Processes in a Magnetic Field - Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Plekhanov V. G.; Bespala E. V. Evgeniy (Evgeny) Vladimirovich; Khan V. A. Valery Alekseevich; Ushakov I. A. Ivan Alekseevich; Baranov E. A. (Plasma, Microwave, Ion, Electron and Isotope Technologies, 2015)
Title screen